Variação sintática das orações adverbiais finais : similaridades e diferenças entre fala e escrita - Deoclécio, Carlos Eduardo (2011)
The aim of this study is to analyze the syntactic variations of final adverbial subordinate clauses, one moment developed, the next reduced, in speech or writing, illustrated in the following examples: “[...] a mãe corta essa ligação para que o filhote aprenda a cuidar de sua vida” (example of final developed clause, from the writing corpus) and “[...] cheguei em casa chorando pra não... pra ela não me bater” (example of final reduced clause, from the speech corpus). This analysis is based on the theoretical-methodological orientation from Variationist Sociolinguistics, mainly in Labov (2008), complemented by the use of the principles from North American Functionalism, such as marking (GIVÓN,1995), economy and iconicity (HAIMAN, 1983). The speech language corpus was composed by 19 interviews from PORTVIX sample (group of interviews held with speakers in the city of Vitória/ES, using the Labovian model), whereas the written language corpus was composed by 35 articles from Superinteressante magazine. The computer program Varbul, version GOLDVARB X (SANKOFF; SMITH; TAGLIAMONTE, 2005), was used to quantify the data obtained in this corpora. This allowed analyzing the data in terms of statistic relevance of the variables which influence the variation of the investigated phenomenon. Overall, the percentage of final developed clauses was 3% in speech and 16% in writing, thus 97% and 84%, respectively. Five independent variables of linguistic nature and three of social character were identified in the study. By meanings of statistics, the program selected the following: for speech data, syntactic-semantic characteristics of the subject in the main clause (with the element of non controlling subject benefitting the final developed clause, occurring 23.1%, relatively 0.94); for writing data, explicitness of the subject in the final adverbial clause (with the element of the explicit subject increasing the final developed ratio to 10.8%, relative weight 0.91); and the informer’s education level (with the element of higher education benefitting the final developed clause, with a frequency of 6.7%, relative weight 0.84); for writing data, the co-referentiability of the subject in the final adverbial, in a sense that final developed are benefitted from the elements of partially co-referential subject (with frequency of 29.6%, relatively 0.81) and non co-referential subject (51.6% of use, relative weight 0.76); and the subject explicitness in the final adverbial clause, in which the element of explicit subject is benefitted from this variation (85.7% of use, relative weight 0.97). In this paper it is understood that the correlation between the (non) co-referentiality and the (non) explicitness of the subject in the final adverbial clauses occurs by economic motivation, in which the former motivates the latter. In addition, the more or less coding of the subject motivates the occurrence of the final developed clause in the first case and the final reduced clause in the second by iconicity. After the results were assessed and analyzed, it was concluded that the syntactic variation of the final adverbial clauses is not a regional phenomenon, for it is aligned to the results found in previously developed studies, such as Finck’s (2000) on speech and Azevedo’s (2000) on writing. Hence, it may be considered a phenomenon which is substantially domestic to the linguistic system of the Portuguese language.